Potential fish-productivity of the North-west part of the Caspian in nowadays conditions - G. M. Abdurakhmanov; V. N. Vinnikova; E. A. Sokolskaya (Юг России: экология, развитие, 2015)
Calculation potential fishermading has been made and change of this indicator on the given site of Caspian sea is shown.